The Effect of Minecraft Video Game on Students’ English Vocabulary Mastery - Imam Sudarmaji; Danu Yusuf (JETAL: Journal of English Teaching & Applied Linguistic, 2021)
Vocabulary mastery is important to acquire a language. Learning vocabulary has several barriers that slow down the progress. Minecraft application is used as a new method of learning English vocabulary. The goal of this research was to investigate whether there is a significance positive effect after used Minecraft application on students’ vocabulary mastery for 5th grade elementary students. A quasi-experimental method was used in this research with 63 students of SDN Poris Plawad 1 Tangerang, which separated into an experimental group (n=31) and a control group (n=32). The results revealed that Minecraft has better score result than the conventional method. Besides, the students’ behavior also resulted to be better than the conventional method. The survey also revealed that the students agreed that Minecraft was making the learning easier, less boring, less stressful and happier. However, the results could not be generalized due to the small sample taken in this research.